Nutritional status of children 2-5 years old, its relation with cow milk consumption and other associated factors in Kilteawlaelo District eastern zone Tigray, Ethiopia - Teklehaymanot, A. (Bahir Dar University, 2015)
Globally malnutrition is responsible for nearly half (45%) of all deaths in children under fiveand responsible for around 3.1 million deaths annually. Agricultural products provideenergy, protein, vitamins and minerals and critical to addressing malnutrition, particularlyamong children. Dairy products play a key role in healthy human nutrition and developmentthroughout life especially, in childhood because of the concentrated source of macro andmicronutrients. The aim of this study was to assess nutritional status of children two to fiveyears’ old, cow’s milk consumption pattern and other associated factors. Community basedcross-sectional survey was conducted in Kilteawlaelo district from April to June 2015. A totalof 530 households were included using two stage sampling technique. Mothers/care giverswere interviewed after consent was given to obtain the information on child care and feedingpractices. Anthropometric measurements were used to assess the nutritional status of children2 to 5 years old. Among the 530 sampled children 19% and 81% was living in urban andrural respectively. The prevalence of stunting, underweight and wasting was 43 %, 26 % and10.9 % respectively. The Bivariate analysis, using chi square test revealed that marital status,occasion of soap use for hand washing, sex of care giver, most commonly consumed cereals,father’s occupation and birthplace showed significant association with all three indicators ofundernutrition. The multivariate analysis using multiple logistic regressions modeldemonstrated that age of children and commonly consumed cereals were significant predictorof stunting and underweight; mother’s educational level was significant predictor of wastingand underweight; sex of child, child vaccination status, source of cow milk and mother’soccupation were significant predictor of wasting only; marital status, occasion of soap use,father’s educational level and birthplace were significant predictor of stunting only; and sexof respondent were significant predictor of underweight only. The results of this studyindicate that under nutrition among 2 to 5 years old children is still a problem in Kilteawlaelodistrict. Child age, mother’s and father’s educational level, mother’s occupation, source ofcow milk, sex of respondent and child, child vaccine, marital status, commonly consumedcereal and occasion of soap use were found to be significant risk factors of malnutrition.